Production of Bio-Oil from Empty Fruitbunch (EFB) via Pyrolysis Process - Muhammad Suhaimi, Man (2013)
The world needs to transition from its current unsustainable energy paradigm to a future powered by entirely renewable energy supply. Only by making such a transition will we be able to avoid the very worst impacts of climate change. We have a lot of EFB produce in Malaysia and it is keep increasing throughout the year. The solution is by recycling the EFB as a raw material for Bio Oil.From the need we see the opportunity to do the bisness. So now we see the market survey of bio oil as a renewable energy. Energy from renewable resources can be increased from 10% today to 30% by 2050. World energy consumption 2005 is 240 Million Barrels of Oil Equivalent which is Biomass covered 10%.World energy consumption in 2050 around 380 Million Barrels of Oil Equivalent and Biomass covered 30%.The market for this industry is large in the future. Then we look to the process in producing of bio oil from Empty Fruit Bunch (EFB). In flash pyrolysis process, the biomass – Empty Fruit Bunches (EFB) was heating in the absence of air or O2 at pyrolysis temperature. The initial products of pyrolysis were comprised of condensable gases and solid char. Then the condensable gases would breaking down further into non condensable gases which were consisted of pyrolysis gases (CO, CO2, CH4 and NH), liquid (Bio Oil)and solid (Bio Char). The selected process had been discussed which included the raw material (EFB) availability in Malaysia, market survey from certain regions, justification of the pyrolysis process, plant feasibility, the suggested location and plant layout. Besides that the feasibility of the plant was analysed from the economic perspective. The economic evaluations which included the cost of major equipments utility cost and other costs are estimated. For the sale forecast we can see that the production unit of Bio Oil is 250 ton/month for first year. The revenue that we get for every month in first year is RM710, 250. Total revenue for first year is RM7, 102,500. For the second year, we increase the unit sale by 25% from the previous year which is 313 ton/month. Revenue for the first month is RM887813 and total annual revenue for second year is RM10, 653,750. In year three, after increase 25% the unit sale is 391 ton/month. Revenue for the first month is RM1,110,831 and total annual revenue for second year is RM13,329,972. In 4th, 3th and 5th years the total annual revenue are RM 16,670,988 and RM 20,830,212 respectively. For profit and lost statement, there was no production in the first two month in year one due to start up period. The net profit in 1st, 2nd and 3rd year is RM 343,565, RM 1,114,669 and RM 1,663,204continuously. For the 4th and 5th years total net profit is RM 2,391,698 and RM3, 305,567 respectively. Then cash flow shows a positive value from starting year until the 5 year. It means the company does not need any external funding for continuing the business. Lastly in financial part is balance sheet. From the beginning until year five, total asset is same with liability and equity. The total Asset for the first year is RM 2,343,566. Total Asset for 2nd year is RM 3,158,241. Total Asset for 3rd year is RM 4,521,440.Total asset for 4 and 5th year is RM 6,613,138 and RM 9,618,705 respectively. For the capital requirement, after doing all the detail expanses in this plant, the total amount that required in this business is around RM2.3 million. From this amount, I will make loan from Bank Negara Malaysia is RM2 million. The balance from the amount we can get from the owners and investor around RM300, 000.So the total capital we get is around RM2.3 million. The payback period we can get in year 2.So as a conclusion this business is feasible to run.